Criminal Liability for Environmental Harm: An Analysis of Environmental Crimes - Gurjar*, Aditya (Trinity Law Review, 2026)
Environmental crimes include a series of illegal activities, such as toxic waste dumping, illegal logging, wildlife poaching, and uncontrolled emissions, which have a direct effect on the environment and human health. In India, the pace of industrialization and socio-economic factors have contributed to such crimes. This paper critically evaluates the types, causes, and effects of environmental crimes in India, analyzes the legal framework (statutes and judicial precedents), and examines the challenges of enforcement. Various Indian laws (Water Act, Air Act, Forest Conservation Act, Environment Protection Act, Wildlife Acts, and so on) and the constitutional provisions (for example, Article 21’s right to a clean environment) are also discussed. Notable judicial precedents (for example, M.C. Mehta vs. Oleum Gas Leak Case and Vellore Citizens’ Welfare Forum) are also examined to highlight judicial advancements. The statistical trends (notably, a 30% increase in environment-related crimes in 2023) emphasize the enforcement deficits. Finally, we present strategies and recommendations, such as the establishment of special eco-crime units, cooperation among agencies, and public awareness, to improve India’s response to environmental crimes. This is a broad analysis that seeks to enlighten policymakers, lawyers, and the general public on how to fight “green crimes” and protect the natural heritage of India.